THE URGENCY OF SHARIA BUSINESS DEVELOPMENT IN THE DIGITAL ERA - Fitri, Mulyana; Sirait, Frida Yanti; Sugianto, Sugianto (Proceeding International Seminar of Islamic Studies, 2024)
In the midst of very rapid development and our current condition in the digital era, sharia economics can increasingly spread its influence throughout the world. The sharia economy with all its infrastructure and instruments must be able to take advantage of this enormous opportunity. The aim of the following research is to analyze the urgency of developing Islamic sharia business in the digital era. The method used is a qualitative method, namely library research. The results of the research are a) Islamic Economics builds the integrity of Muslims who run the economy in accordance with Islamic teachings, b) Makes people accustomed to carrying out religious activities in the context of economic activities, c) Supports efforts to empower the economy of Muslims and develop Muslim businesses, d) Practicing sharia economics or Islamic economics means supporting the amar ma'ruf nahi mungkar movement. The research conclusion is that digitalization of sharia business development is very essential because it has a good impact on every business or agency. The government also provides very positive support through technological infrastructure, economic development, especially digitalization of sharia business.